Covid -19, gender and health: Recentring women in African indigenous health discourses in Zimbabwe for environmental conservation - Manyonganise, Molly (HTS teologiese studies, 2023)
In precolonial Africa, women were the major authorities in herbal remedies within their own homes and at the community level, where they focused on disease prevention and cure. Such roles were pushed to the periphery of Africa’s health discourse by the introduction of Western modes of healing. Furthermore, missionaries branded African indigenous medicine (AIM) as evil and categorised it within the sphere of witchcraft. However, the emergence of new diseases which conventional medicine has found difficult to cure seems to have caused Africans to rethink their position on AIM. For example, there appears to have been a resurgence of interest in utilising AIMs during the coronavirus disease 2019 (COVID-19) pandemic. Greater utilisation, while positive, may lead to herbs and plants becoming extinct if the harvesting is done haphazardly. Therefore, the intention of this article is to examine the intersections of gender and health in the COVID-19 context. The article seeks to establish the role that was and continues to be played by women in the utilisation of AIM within the context of COVID-19. The focus of the paper is on finding out the ways in which women are safeguarding plants and trees whose leaves, roots and barks are envisioned as effective in preventing infection as well as curing the disease. Data were gathered through informal interviews. Theoretically, the article makes use of gender and Afrocentricity as theories informing the study.Contribution: The article highlights the need for placing women at the centre of both health and environmental discourses for sustainable development. It argues for the recentring of women in Earth discourses. Hence, its contribution is in retrieving women’s voices in health and Earth discourses in Zimbabwe for sustainable development to be achieved.